Insulin Resistance and Oxidative Stress: In Relation to Cognitive Function and Psychopathology in Drug-Naïve, First-Episode Drug-Free Schizophrenia - Tao, Qi; Miao, Yu; Li, Huihui; Yuan, Xiuxia; Huang, Xufeng; Wang, Yunpeng; Andreassen, Ole A.; Fan, Xiaoduo; Yang, Yongfeng; Song, Xueqin (Frontiers in Psychiatry, 2020)
Objective The present study aimed to examine whether insulin resistance and oxidative stress are associated with cognitive impairment in first-episode drug-free schizophrenia (SZ) patients. Methods Ninety first-episode SZ patients and 70 healthy controls were enrolled. Homeostatic model assessment of fasting plasma glucose (FPG), fasting insulin (FINS)), and markers of oxidative stress (oxidized glutathione (GSSG), superoxide dismutase (SOD), nitric oxide (NO) and uric acid(UA) levels) were measured in serum before pharmacological treatment was initiated. Psychiatric symptoms and cognitive function were assessed with the Positive and Negative Syndrome Scale (PANSS) and MATRICS Consensus Cognitive Battery (MCCB) respectively. In addition, the homeostatic model assessment of insulin resistance (HOMA-IR) was also studied. Results HOMA-IR and serum levels of GSSG and NO were significantly higher in SZ patients than in healthy controls (P<0.001), while the serum levels of SOD were significantly lower than in healthy controls (p<0.001). HOMA-IR, GSSG and NO levels were significantly related to the total cognitive function scores of the patient group（r=-0.345,-0.369,-0.444, respectively ,P<0.05）, but they were not related to the healthy control group, while SOD, UA and the total cognitive function scores of the patient group and the healthy control group were not related. NO was positively correlated with general pathological and the total score in the PANSS, and was negatively correlated with six cognitive domains (r = -0.316 to -0.553, P<0.05). Conclusions The levels of insulin resistance and oxidative stress are elevated, and correlated with the severity of cognitive impairment in patients with drug-naïve, first-episode SZ patients. Treatment approaches targeting to reduce insulin resistance and oxidative stress may improve cognitive function in this patient population.